2012
DOI: 10.1097/mjt.0b013e3182456a61
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plasma Methionine–Enkephalin Levels in Cluster Headache Patients

Abstract: Results from a longitudinal study (blood drawn at days 29, 64, 89,124, 142, and 182 of the protocol) shows that the concentration of platelet-poor plasma (PPP) methionine(5)-enkephalin (MET) in healthy, drug-free, white male individuals (n = 5) remains within a relatively narrow range, well within the experimental error of the analytical procedures used. Interindividual differences fail to reach statistical significance [x ± SD and range (MET picograms per mL of PPP) of 91.2 ± 15.1, 67.1-113.5; 69.6 ± 7.5, 66.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
1
1
Order By: Relevance
“…Of interest, it was noted that systemic insulin-at dosages utilized to maintain normal blood glucose-was reported to provide protection against delayed re-epithelialization of corneal abrasions that is normally seen in diabetic rats, 12,15 but did not protect against dry eye or abnormal surface sensitivity in these animals. This is in contrast to a study where topical insulin was applied as a therapy for delayed healing [24][25][26][27] and changes were noted in sensitivity relative to diabetic rats.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Of interest, it was noted that systemic insulin-at dosages utilized to maintain normal blood glucose-was reported to provide protection against delayed re-epithelialization of corneal abrasions that is normally seen in diabetic rats, 12,15 but did not protect against dry eye or abnormal surface sensitivity in these animals. This is in contrast to a study where topical insulin was applied as a therapy for delayed healing [24][25][26][27] and changes were noted in sensitivity relative to diabetic rats.…”
Section: Discussioncontrasting
confidence: 74%
“…At this time no data are available on OGFr levels in diabetic humans. Whether the changes observed for rats are consistent with humans awaits further reseach as studies have shown that plasma OGF levels do fluctuate with different pathologies 19,24,25,26,27 Our data demonstrate a dysregulation in the OGF-OGFr axis with increases in corneal epithelial levels of the inhibitory peptide OGF and its receptor in both controlled and uncontrolled diabetic corneal epithelium. Likewise, noninvasive measures of the ocular surface (e.g.…”
Section: Discussionsupporting
confidence: 52%
“…Fernández et al observed widespread pressure pain hypersensitivity in patients with cluster headache, compared with healthy controls [93]. In addition, cluster headache patients were observed having decreasing plasma methionine-enkephalin levels [94]. However, lower CSF met-enkephalin levels in patients with cluster headache can be increased by manual acupuncture or EA [95].…”
Section: Methodsmentioning
confidence: 99%